Teams composition of the psychosocial attention centers in southern brazil - Denise Silva da Silveira; Michele da Silva Corrêa; Mirelle Oliveira Saes; Luciane Kantorski; Vanda Jardim; Cristiane Quadrado da Rosa (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769210013 Aims: describe the composition of the teams of the Center of Psychosocial Attention (CAPS), according to sociodemographic characteristics, work, training and professional qualification and thus contribute to the evaluation of the public investment in the management of work and continuing education. Methods: it is a cross-sectional study integrated to the research "Evaluation of CAPS in southern Brazil". Results: the majority of the workers were women (78%), with higher education, with an average workload of 30 hours weekly, with a single job. About 30% had poor working relationship. We found a low percentage of doctors (62%) and nurses (26%) specializing in mental health and quantitative deficiency of midlevel and technical professionals in the health teams (53%). Conclusions: we emphasize the importance of adequate training of the teams and the need to fight precarious work. The results suggest a gap to be filled into what is advocated for the CAPS's workforce composition.